Efeitos da distribuição de manchas de folhas na estrutura de macroinvertebrados de riachos - Hanashiro, Fábio Toshiro Taquicava (Universidade Federal de São Carlos, 2010)
To understand the effects of spatial heterogeneity on the processes that determine the distribution of organisms in low-order streams, in the present study we asked the following question: do the composition and spatial arrangement of leaf litter patches at the scale of streambed landscapes influence the structure and composition of aquatic macroinvertebrate communities? We evaluated substrate organization in two distinct phases: an initial description of the streambeds using landscape ecology techniques, and a second, experimental phase studying the response of aquatic macroinvertebrates to manipulated distributions of the substrate. The results of the descriptive phase showed the importance of leaf litter substrate influencing taxon richness, diversity, evenness, and abundance; further, the division of the habitat in patches was also important to structure the macroinvertebrate communities. The experimental manipulation showed that resource aggregation influences the colonization of the community, mainly in the early periods (8 days). In general, the influence of resource spatial distribution had different effects between the two approaches used, probably due to differences in patch size and quality. The results of the present study can contribute to a better comprehension of the mechanisms structuring the communities of aquatic macroinvertebrates, and to the improvement of sampling techniques and stream restoration projects.
Keywords: Ecologia; Insetos aquáticos; Substrato; Ecologia da paisagem; Dinâmica de manchas; Macroinvertebrados aquáticos; Riachos; Patch dynamics; Aquatic macroinvertebrate; Streams; Substrates types; CIENCIAS BIOLOGICAS::ECOLOGIA